Alpe kot območje kulturnega, družbenega in političnega stika - Bufon, Milan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 1999)
The article deals with the Alps as an area of both cultural, social and political contact and division. From this perspective the relation between different "border lines", which can be detected in the alpine regions, is examined, suggesting that all these "border lines" maz be seen as a result of a complex relationship between spatial, social and cultural partition and integration processes. As a result, the Alps represent a special and particularlz interesting natural, social and cultural environment in which processes of social and political moderniyation maz coexist with persistent forms of cultural and territorial identitz, but also with different forms of functional social and spatial cooperation on an international and inter-regional level. The article finallz opens up the question of how traditional forms of social and cultural coexistence in the Alps are now challenged bz a growing demand for social and spatial integration.
Keywords: Alpe; Alps; družbena geografija; družbeni razvoj; gospodarski razvoj; human geography; obmejna območja; regional geography; regionalna geografija; regionalni razvoj; sonaravni razvoj